A Review of Feeding Practices in Infants With Neonatal Abstinence Syndrome. (December 2020) - Taylor, Kailey; Maguire, Denise
Abstract : Background: There has been an increase in infants with neonatal abstinence syndrome (NAS) in neonatal intensive care units (NICUs) over the past several decades. Infants with NAS experience withdrawal as a result of the sudden termination at birth of substance exposure during pregnancy. A serious sign related to infants diagnosed with NAS is poor feeding. The prevalence of NAS urges researchers and clinicians to develop effective strategies and techniques to treat and manage the poor feeding of infants exposed to substances in utero. Purpose: To synthesize current feeding methods and practices used for infants diagnosed with NAS. Methods/Search Strategy: PubMed, CINAHL, and Scopus were searched for articles published within the last 20 years that focused on feeding practices or feeding schedules, were written in English, were peer-reviewed, and described human studies. The search terms utilized were "neonatal abstinence syndrome" OR "neonatal opioid withdrawal syndrome" AND "feeding." Findings/Results: Three findings emerged regarding techniques and management of poor feeding in the NAS population. The findings included infants who received mother's own milk had decreased severity and later onset of clinical signs of withdrawal, demand feeding is recommended, and the infant's cues may be helpful to follow when feeding. Implications for Practice: Clinicians should encourage mother's own milk in this population unless contraindications are present. Caregivers and clinicians must be receptive to cues when feeding infants with NAS. Implications for Research: Even with the clinical knowledge and experience that infants with NAS are difficult to feed, there is limited research assessing techniques and schedules that are effective in managing successful feeding. Future research should compare feeding schedules such as on-demand feeding versus regimented feeding schedules, as well as investigate techniques that mothers and nurses can utilize to encourage oral intake in this population. Video abstract available at https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx?autoPlay=false&videoId=37 Abstract : Supplemental Digital Content is Available in the Text.